Non-surgical management of congenital ichthyosis using hyaluronic acid gel injection. Issue 1 (January 2020) - Cicinelli, Maria Vittoria; Dave, Tarjani Vivek; Madhuri, Bejanki Kavya; Tiple, Sweety; Naik, Milind N
Aim: To test if hyaluronic acid gel injection in the upper eyelid achieves correction of congenital cicatricial ectropion and reduction in lagophthalmos, in preparation for intraocular surgery. Methods: This case reports the long-term outcome of hyaluronic acid gel injection in the upper eyelid for the correction of ectropion prior to cataract surgery. One millilitre of hyaluronic acid gel was injected in both the upper eyelids of a child with congenital ichthyosis in the suborbicularis plane, prior to cataract surgery. Results: Lagophthalmos reduced by 15 mm in the right eye and 13 mm in the left eye. Subsequently, the child underwent cataract surgery without any complications. Conclusion: We demonstrate the long-term outcome of using hyaluronic acid gel injection for successful, non-surgical correction of cicatricial ectropion in ichthyosis.